2019
DOI: 10.1007/s40544-017-0309-0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical study on surface roughness of magnetorheological elastomer for controllable friction

Abstract: Magnetorheological elastomer (MRE) is a type of smart material of which mechanical and electrical properties can be reversibly controlled by the magnetic field. In this study, the influence of the magnetic field on the surface roughness of MRE was studied by the microscopic modeling method, and the influence of controllable characteristics of the MRE surface on its friction properties was analyzed by the macroscopic experimental method. First, on the basis of existing studies, an improved mesoscopic model base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…The rationale of the HPS is to determine the coefficient of friction by dividing the horizontal pull force by the gravity of the weight unit. This is similar to that of the sliding friction tester in the literature [41].…”
Section: Friction Measurement Devicesupporting
confidence: 85%
“…The rationale of the HPS is to determine the coefficient of friction by dividing the horizontal pull force by the gravity of the weight unit. This is similar to that of the sliding friction tester in the literature [41].…”
Section: Friction Measurement Devicesupporting
confidence: 85%
“…In general, the change rate of the elastic modulus of MRE under magnetic field is relatively high, which can increase 123% [26]. Although the surface morphology of the MRE is also controlled by the magnetic field to produce changes [24], compared with the changes in the elastic modulus, the range of surface morphology changes is smaller, which only within 30%. Since 1 and 2 are positive constants, the influence degree of elastic modulus is greater than that of surface roughness, so the changing trend of MRE friction force mainly depends on the magnetic-controlled elastic modulus, and the influence of magnetic-controlled surface morphology is relatively small.…”
Section: Figurementioning
confidence: 99%
“…On this basis, our research group [19,20] derived that there maybe some trend between the friction coefficient of the isotropic MREs and the elastic modulus by combining the elastic contact theory. Meanwhile, our research group [24] found that the surface morphology of the MREs also changed with the magnetic field, and the surface roughness can affect the friction characteristics. In addition to the mechanical properties of the contact surface, the topographical features of the surface and modulus are also important factors affecting the friction characteristics [25].…”
Section: Introductionmentioning
confidence: 98%